Simultaneous Analysis of Tablets Content Vitamin C And Zinc In Visible Spectrophotometry - Sulasmi, Sulasmi; Muchlisyam, Muchlisyam; Haro, Ginda (Publisher Cv. Inara, 2023)
Most drugs on the market contain multiple active ingredients, each of which is intended to enhance the drug's therapeutic effect and ease of administration. Determination of the levels of efficacious substances in drug preparations is essential for agencies that conduct drug determinations, such as the Food and Drug Supervisory Agency (BPOM) and the drug industry; therefore, a rapid and dependable analytical method, as well as relatively inexpensive and easily accessible tools and operational costs, are required. In practice, however, it can produce accurate and precise results. This research will be conducted by optimizing the solvent and simultaneously analyzing the levels of Vitamin C and Zinc in the tablet preparation without any separation step using visible spectrophotometry. Vitamin C and Zinc were found to be soluble in a mixture of methanol and water with a ratio of 50:50 after a single examination with the addition of the complexing agent dhitizon at a concentration of 0.1%, which produced a pink color. Calculation of Vitamin C and Zinc's linearity. The linearity value described is the correlation coefficient value for both Vitamin C and Zinc, which is very close to one, indicating an excellent relationship between the drug concentration and the absorbance value. This also suggests that absorbance will increase as concentration increases. The method validation requirements for linearity, accuracy, and precision as well as the limit of detection (LOD) and the limit of quantification (LOQ) were met by the analytical method validation with promising results.